2020
DOI: 10.1038/s41467-020-14383-0
|View full text |Cite
|
Sign up to set email alerts
|

Possible Luttinger liquid behavior of edge transport in monolayer transition metal dichalcogenide crystals

Abstract: In atomically-thin two-dimensional (2D) semiconductors, the nonuniformity in current flow due to its edge states may alter and even dictate the charge transport properties of the entire device. However, the influence of the edge states on electrical transport in 2D materials has not been sufficiently explored to date. Here, we systematically quantify the edge state contribution to electrical transport in monolayer MoS 2 /WSe 2 field-effect transistors, revealing that the charge transport at low temperature is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…systems, including metallic carbon nanotubes [15][16][17] , nanowires 18 , and edge states in 2D systems, have been reported as LLs and show good agreement with theory 19,20 . Although isolated polymer chains have quasi-1D structures, their films are usually in condensed 2D or 3D forms, and these undoubtedly raised questions on whether the conducting polymer could be treated as collections of pure 1D LL systems without considering their detailed condensed forms on the molecular scale.…”
Section: Introductionsupporting
confidence: 55%
“…systems, including metallic carbon nanotubes [15][16][17] , nanowires 18 , and edge states in 2D systems, have been reported as LLs and show good agreement with theory 19,20 . Although isolated polymer chains have quasi-1D structures, their films are usually in condensed 2D or 3D forms, and these undoubtedly raised questions on whether the conducting polymer could be treated as collections of pure 1D LL systems without considering their detailed condensed forms on the molecular scale.…”
Section: Introductionsupporting
confidence: 55%
“…However, LL theory usually relates to strict onedimensional (1D) systems with strong electron correlation, and its nonlinear current-voltage (I-V) behaviors usually stem from the power-law type density of states (DOS) near the Fermi level. Several pure 1D systems, including metallic carbon nanotubes [16][17][18] , nanowires 19 , and edge states in 2D systems, have been reported as LLs and show good agreement with theory 20,21 . Although isolated polymer chains have quasi-1D structures, their films are usually in condensed 2D or 3D forms, and these undoubtedly raised questions on whether the conducting polymer could be treated as collections of pure 1D LL systems without considering their detailed condensed forms on the molecular scale.…”
mentioning
confidence: 57%
“…These results were corroborated by DFTcalculations were up to two intrinsic metallic edge states were found, associated with subtle changes in the electronic structure close to the edge. A subsequent study [49] demonstrated that the edge transport plays a dominant role over bulk transport at low temperatures down to 6.3K. Other work [17] investigated the conducting properties of atomically thin layers of MoS 2 tuned by gate voltages.…”
Section: Summary and Discussionmentioning
confidence: 99%